Ferroptosis-associated signaling pathways and therapeutic approaches in depression - Xuyang Feng; Xuyang Feng; Xuyang Feng; Wenyu Zhang; Wenyu Zhang; Wenyu Zhang; Xiaoxi Liu; Xiaoxi Liu; Qiuxuan Wang; Qiuxuan Wang; Qiuxuan Wang; Xiao Dang; et al. (Frontiers in Neuroscience)
Ferroptosis, a newly identified form of cell death, is characterized by excessive iron accumulation and lipid peroxidation. Studies indicate a strong association between ferroptosis and depression; however, the precise signaling pathways and underlying molecular mechanisms remain unclear. This review summarizes the role of ferroptosis in depression and its associated signaling pathways. Additionally, therapeutic approaches for depression based on ferroptosis theory are reviewed, providing novel targets for the prevention and treatment of depression and laying a foundation for future research on the relationship between ferroptosis and depression.